The Guide to Gethsemane : Anxiety, Suffering, Death - Falque, Emmanuel, 1963- (Book collections on Project MUSE., 2019)
Already widely debated upon its publication in French, this text offers a provocative account of Christ's Passion in terms not of faith but of a 'credible Christianity' that can remain meaningful to nonbelievers. For Falque, anxiety, suffering, and death are not simply the 'ills' of our society but the essential horizon of what we confront as humans. Doubtful of Heidegger's famous statement that the notion of salvation renders Christians unable authentically to experience anxiety in the face of death, Falque explores the Passion with a radical emphasis on the physicality and corporeality of Christ's suffering and death, and on continuities with the mortality of our bodies. Written in the wake of a friend's death, Falques's study is theologically and philosophically rigorous, yet engagingly written and deeply humane.